Cholecystokinin octapeptide-like immunoreactivity: histochemical localization in rat brain. - Innis, R B (1979)
Cholecystokinin octapeptide-like (CCK-OP-like) immunoreactivity was localized in the rat brain by using the indirect immunofluorescence method. Specificity in immunohistochemical studies was demonstrated by the virtual elimination of staining with either preimmune sera or sera preadsorbed with CCK-OP and by the achievement of similar fluorescent patterns with two different primary anti-CCK-OP sera. CCK-OP-like fluorescence was localized in neuronal cell bodies, fibers, and varicose terminals. The most dense collections of CCK-OP cells occurred in the periaqueductal gray and in the dorsomedial hypothalamus. Substantial numbers of cells and fibers also were present in the medial/dorsal and perirhinal cortex; more limited groups of cells were found in the pyramidal layer of the hippocampus and in the dorsal raphe.